Penentuan Kebutuhan Proteksi Petir pada Gedung Bertingkat Kantor BPJS Ketenagakerjaan Cabang Blitar. - Prasetyo, Robin (Jurnal Qua Teknika, 2017)
Lightning is natural phenomenon that is the result of electrostatic events in the cloud for their difference in charge between the clouds or the difference in charge between the cloud and the earth and become involved in the discharge and generate an electric arc that we can see as lightning. To protect the building from the danger of lightning strikes the lightning rod should be installed so that the building and electrical devices that are in, it are protected from over voltage from lightning strikes them. The finial project will discuss the calculation and the elevation of the external lightning protection system that has existed in the building of the Office of Employment Branch BPJS Blitar and compare it with the existing theories regarding the calculation of the lightning rod. From the calculation and elevation by the author can be concluded that the lightning rod mounted on the Office of Employment Branch BPJS Blitar cannot protect the building properly.